Factorial Experiment Study on the Mechanical Properties of Sandstone–Concrete Specimens Under Different Freeze–Thaw Conditions - Zhao, Tao; Yang, Gengshe; Xi, Jiami; Shen, Yanjun; Song, Ki-iL (Frontiers in Physics, 2020)
The contact part between shaft wall and rock is affected by many factors, such as temperature, formation pressure and so on, in the commonly used freezing method in coal mine development through quicksand and water-rich strata. In order to confine the relationships between these factors and the compressive strength of the contact surface, the sandstone which contacts with the outer well wall was selected in this study to prepare a complex of sandstone and C40 concrete mortar. The factorial design of the multi-factors affecting the uniaxial compressive strength of the complex specimens based on the freeze-thaw cycles test, the uniaxial compression test and the statistical principle was used to study the interactive effect of various factors. Significant analysis was performed via analyzing the sample water content, the freezing temperature and the number of freeze-thaw cycles based on the factorial design principle. The results show that the uniaxial compressive strength (UCS) of the dry sandstone-concrete complex specimens is significantly higher than that of the water-saturated sandstone-concrete complex specimens. After freeze-thaw cycles, the UCS of both the dry sandstone-concrete complex specimens and water-saturated sandstone-concrete complex specimens decrease significantly. In addition, the significant effects of main effect and primary and secondary interaction on unconfined compressive strength were obtained, and the major interaction among the factors was synergistic interaction, and the minor interaction among the factors is non-interactive interaction and antagonism.